2018
DOI: 10.1155/2018/8507567
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Antimicrobial Studies of Novel Series of 2,4-Bis(hydrazino)-6-substituted-1,3,5-triazine and Their Schiff Base Derivatives

Abstract: The present work represents the synthesis, characterization, and antimicrobial studies of novel series of 2,4-bis(hydrazino)-6substituted-1,3,5-triazine and their Schiff base derivatives. IR, NMR ( 1 H and 13 C), elemental analysis, and LC-MS characterized the prepared compounds. The biological activity of the target products was evaluated as well. Twenty-two of the prepared compounds were selected according to their solubility in aqueous DMSO. Only eight compounds showed good activity against the selected pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…First, compounds 2a-c were prepared as described in Method S1 (Supporting information) following the reported methods [41,44]. The NMR spectra agreed with the reported data (Supporting information, Figures S1, S2 and S3).…”
Section: Synthesis Of 24-bishydrazino-6-substituted S-triazine Deriva...supporting
confidence: 65%
See 2 more Smart Citations
“…First, compounds 2a-c were prepared as described in Method S1 (Supporting information) following the reported methods [41,44]. The NMR spectra agreed with the reported data (Supporting information, Figures S1, S2 and S3).…”
Section: Synthesis Of 24-bishydrazino-6-substituted S-triazine Deriva...supporting
confidence: 65%
“…In this regards, and in continuation of our previous work [44,45], we describe herein the synthesis and characterization of two groups of charring agent based on polymers containing s-triazine with hydrazine and hydrazido linkage in their backbone chain. The described derivatives have aniline, p-bromoaniline, p-methoxyaniline, linked to the striazine ring.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Cyanuric chloride has been used as building blocks in the synthesis of vast derivatives bearing the s-triazine moiety, due to the low-cost, commercial availability, and ease of displacement of the three chlorine atoms by various nucleophiles under controlled temperature [24]. ese advantages allowed for the preparation of mono-, di-and trisubstituted s-triazines derivatives with a wide range of biological activities [25][26][27], such as adenosine receptor antagonist [28], antiamoebic [29], antileishmanial [31][32][33], anticancer [32], antimalarial [34], antimicrobial [35][36][37], antiviral [38], antitubercular [39], carbonic anhydrase inhibitor [40], and cathepsin B inhibitor [41], Previously, we reported new series of s-triazine Schiff-base derivatives [42][43][44]; among of the reported compounds, only three derivatives were able to inhibit the growth of lung (A549) and hepatocellular carcinoma (HepG2) cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The 1,3,5-triazine were found to demonstrate significant activity on bacteria in microgram/ml range, but no antifungal activity was observed. It may be suggested that the presence of 1,3,5-triazine in the mistletoe contributed to the observed activity against the gram positive bacteria [17].…”
Section: Discussionmentioning
confidence: 99%